Development of E-Book On Osmotic Pressure Materials For Online Learning During The Covid-19 Pandemic - Dwi Rexana Putri; Nina Kadaritna; Emmawaty Sofya (Universitas Lampung, 2021)
In December 2019, there was an outbreak of a virus known as Covid-10. To prevent the spread of Covid-19 in Indonesia, the government made a Work From Home (WFH) policy. The existence of this WFH policy has an impact on the education sector, namely on the implementation of teaching and learning activities which were originally face-to-face to be changed online. Online learning on osmotic pressure material is still lacking in resources. The purpose of this research was to develop an e-book on the subject of osmotic pressure, describe the validity, teacher responses, and student responses. The research method used is Research and Development according to Borg and Gall until the fifth stage. The results of expert validation of e-books on aspects of the suitability of the content of the material, aspects of readability, and aspects of design attractiveness obtained high criteria. The results of the teacher's responses on the attractiveness aspect of the material content, the readability aspect, and the attractiveness aspect obtained very high criteria. The results of student responses on the readability aspect and the attractiveness aspect obtained very high criteria. Based on the results of the study, the e-books on the material of osmotic pressure generated from this study is valid.Keywords: Covid-19, Corona Virus Disease, Work From Home, E-book,Osmotic Pressure DOI: 10.23960/jppk.v10.i3.2021.05